STABILITY ANALYSIS OF NINE PROMISING CLONES OF TEA (Camellia sinensis) - Murti, Rudi Hari; Puspitasari, Ani; Mitrowihardjo, Suyadi (Faculty of Agriculture University of Brawijaya in collaboration with PERAGI, 2014)
There are many clones grown in Indonesia tea plantations. The latest clones were released around 1990. The new promising clones have been bred through crossing among selected clones in Pagilaran tea plantation. The experiment aimed to select high yield and stable clone. Nine clones were grown in Kayulandak (1300 m asl) and Andongsili (1100 m asl) in Randomized Completely Block Design with three replications. The data of fresh weight per plot in 2007, 2008, 2009, 2011, 2012 were recorded. Eberhart & Russell (1966) and GGE Biplot analysis method was applied for data analyzing. The result showed that all of clones were stable over years in each location except for PGL1 and PGL3 in Andongsili and PGL15 in Kayulandak based on Eberhart & Russell analysis. Significant regression coefficient (1.18) of PGL3 implied that PGL3 was high in yield and responsive. GGE biplot analysis indicated no ideal genotype for each location. PGL10, PGL3, PGL4 and PGL 12 were recommended for Kayulandak, while PGL3 and PGL12 clones were suitable for Andongsili. Both analysis of Eberhart & Russell and GGE biplot showed PGL3 and PGL12 as ideal clone, while PGL10, PGL4, and PGL 15 clone were desireable clones.Keywords : Eberhart and Russell, GGE Biplot, tea clones, yield stability